INTRODUCTION TO LEAN CONSTRUCTION - Ismail Abdul Rahman; Aftab Hameed Memon; Ahmad Mujahid Ahmad Zaidi (2011)
Construction industry is one of the most complicated and fragmented industries. It is very unique industry and facing many problems. One of the successful approaches adopted to address these problems is lean construction. Lean construction is a new way to manage construction projects that makes significant improvements on complex, uncertain and quick projects. Lean Construction was proposed from Lean philosophies and theories that have offered lots of benefits to the manufacturing industry. Lean is about doing more with less time, inventory, space, labour, and money. Lean production is a systematic elimination of waste (i.e. overproduction, waiting, transportation, inventory, and over-processing, defective units) and the implementation of continuous flow and customer pull.